Study of genetic parameters for pre-weaning growth traits in inner Mongolia white Arbas cashmere goats - Wang, Ruijun; Liu, Yan; Shi, Yue; Qi, Yunpeng; Li, Yanbo; Wang, Zhiying; Zhang, Yanjun; Zhao, Yanhong; Su, Rui; Li, Jinquan (Frontiers in Veterinary Science, 2023)
The present study was carried out to estimate variance components of pre-weaning growth traits of Inner Mongolia Arbas white cashmere goats (IMWACGs). . The birth weight (BWT), weaning weight (WWT), average daily gain from birth to weaning (ADG) and Kleiber ratio (KR), were based on 21 years (1998–2018) data from Inner Mongolia Yiwei White Cashmere Goat Co., Ltd, Inner Mongolia, China. The parameters were estimated using AIREML method and WOMBAT software. The most appropriate model was chosen by Likelihood ratio test, fitting six animal models excluding or including maternal genetic or maternal permanent environmental effects. The model included the fixed or covariate effects of sex, birth type, birth herds, birth year, birth month, age of dam and some significant interactions among these factors as well as age of weaning. With the best model (Model 6), heritability estimates were 0.0435, 0.0911, 0.0932 and 0.2339 for BWT, WWT, ADG and KR traits, respectively. Maternal heritability estimates were 0.0143, 0.0246, 0.0220 and 0.0186 for BWT, WWT, ADG and KR traits, respectively. The correlation between different traits were estimated with the most suitable model by using bivariate analysis method. The direct additive genetic correlation among the traits ranged from -0.026 (BWT~KR) to 0.772 (ADG~KR). The maternal permanent environment correlation is between -0.289 (BWT-KR) ~0.900 (WWT-ADG). Results indicated that maternal effects and direct-maternal genetic covariance should be considered in any program aimed at improving pre-weaning growth traits to have an accurate genetic evaluation. In addition, positive and medium to high genetic correlations generally exist among WWT, ADG and KR due to the existence of genetic variation for early growth traits. It can be concluded that the genetic progress of these traits can be achieved by selection in the IMWACGs.